(untitled) (Economic studies journal, 2024)
The research aimed to achieve a primary goal of identifying Blockchain technology as one of the latest technologies in the field of technology and communications and highlighting its expected contribution with regard to recording and documenting financial transactions, processing financial transactions measuring them in accounting, and presenting and disclosing financial transactions. The research used the descriptive approach in describing the expected contribution of a Blockchain in accounting, by surveying the opinions of faculty members in accounting departments during the fall semester of 2022-2023 AD in universities and colleges of accounting in the city of Tripoli. These opinions were obtained and the research data was collected using a questionnaire containing a set of Closed-ended questions formulated based on accounting literature, and the data were analyzed using descriptive statistics tools, measures of central tendency, and measures of dispersion. The research concluded that there is a group of faculty members in accounting departments at universities and colleges in the city of Tripoli who do not have sufficient knowledge of blockchain technology. As for the group that had sufficient knowledge of the technology, they saw that the technology contributes to increasing the accuracy and integrity of accounting recording and reducing the margin of error in it. It provides a new mechanism for recording and documenting financial transactions, namely Triple Entry, and reduces the risks of data recovery and corruption and the risks of data manipulation. It creates new types of risks, raises new measurement issues related to encrypted digital assets, and improves the level of disclosure and transparency in financial reports.